The " ambivalence of the sacred" in Africa: the impact of religion on peace and conflict in Sub-Saharan Africa - Basedau, Matthias (GIGA working papers, 2008)
Given the widespread focus on socioeconomic factors, it comes as no surprise that religion is neglected in most theoretical explanations of African civil conflicts. While scholarly interest is increasing in light of the civil wars in Sudan, Nigeria, and northern Uganda, no systematic empirical analysis has been undertaken to date. Hence, this paper aims to provide a preliminary assessment of the role of religions in sub-Saharan civil conflicts. Quantitative and qualitative analysis based on a newly compiled database including 28 violent conflicts show that religion plays a role more frequently than is usually assumed and that the effects of religions are principally ambiguous. Religious actors and institutions have escalating effects in many cases, yet more often they become active for peace. Religious identities and ideas seem to have a particular impact on conflict. Even though religion seems secondary when compared to classical "risk factors", the findings demonstrate that religious factors have to be taken seriously when analyzing civil conflicts in Africa. -- Religion ; Africa ; ambivalence ; civil war ; violent conflict